Legal Protection of Banking Customers Who Are Victims Of Information And Electronic Transaction Crimes - Ibrahim, Dicky Malik; Hidayat, Yusuf; Wasitaatmadja, Fokky Fuad (Universitas Medan Area, 2024)
This research stems from academic concerns about how legislative regulations maintain customers' security affected by crimes in electronic transactions and information in the banking sector, furthermore, regarding the legal protection of banking customers who are victims of information and electronic transactions crime. This study aims to determine and examine the legal protection of customers who are victims of information and electronic transaction crimes. The research method used is normative juridical research using a statutory and conceptual approach. The results showed that 1) Legislation protecting banking customers who are victims of information and electronic transactions crime in the banking sector has previously been regulated in Law Number. 8 of 1999 concerning Consumer Protection and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. 2) Legal protection of banking customers who are victims of information crime and electronic transactions consists of repressive and preventive legal protection. Repressive protection is given when preventive protection cannot prevent customers from Information and Electronic Transaction crimes. In Article 4, letter d of Law Number 8 of 1999 concerning consumer protection, consumers have the right to be heard for their opinions and complaints about the goods or services used. Furthermore, Article 32 of Financial Services Authority Regulation (Peraturan Otoritas Jasa Keuangan / POJK) Number 1/POJK.07/2013 on Consumer Protection in the Financial Services Sector states that financial services business actors are required to have and implement service and settlement mechanisms for consumers. In addition to repressive protection, there is also preventive customer protection listed in Article 4 of the consumer protection law, which states that banks have an obligation to provide guidance and education for customers as consumers